2018
DOI: 10.1080/15384101.2018.1542895
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Up-regulation of microRNA-497 inhibits the proliferation, migration and invasion but increases the apoptosis of multiple myeloma cells through the MAPK/ERK signaling pathway by targeting Raf-1

Abstract: Up-regulation of microRNA-497 inhibits the proliferation, migration and invasion but increases the apoptosis of multiple myeloma cells through the MAPK/ERK signaling pathway by targeting Raf-1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…This causes phosphorylation and inactivation of YAP, a transcriptional coactivator downstream of the Hippo signaling pathway, and antagonization of the function of the Hippo effector, TAZ (17). Knockout of the FAT1 gene increases the nuclear accumulation of YAP and promotes the nuclear and cytoplasmic shuttling of the transcriptional activator TAZ, thereby upregulating the transcription of the Hippo target genes connective tissue growth factor and ankyrin repeat domain 1, which is also accompanied by an increase in the nuclear levels of SMAD2/3 ( (58)(59)(60). It was revealed that FAT1 mutations in pituitary spindle cell tumor were associated with increased MAPK activity, based on the phosphorylation of ERK (p-ERK1/2), highlighting an association between FAT1 and the MAPK signaling pathway (61).…”
Section: Signaling Pathways and Mechanismsmentioning
confidence: 99%
“…This causes phosphorylation and inactivation of YAP, a transcriptional coactivator downstream of the Hippo signaling pathway, and antagonization of the function of the Hippo effector, TAZ (17). Knockout of the FAT1 gene increases the nuclear accumulation of YAP and promotes the nuclear and cytoplasmic shuttling of the transcriptional activator TAZ, thereby upregulating the transcription of the Hippo target genes connective tissue growth factor and ankyrin repeat domain 1, which is also accompanied by an increase in the nuclear levels of SMAD2/3 ( (58)(59)(60). It was revealed that FAT1 mutations in pituitary spindle cell tumor were associated with increased MAPK activity, based on the phosphorylation of ERK (p-ERK1/2), highlighting an association between FAT1 and the MAPK signaling pathway (61).…”
Section: Signaling Pathways and Mechanismsmentioning
confidence: 99%
“…It has been noted in a previous study that the inhibitory role of miR-195-5p in the stem-like ability of colorectal cancer cells [ 8 ]. Moreover, miR-497 could serve as an anti-tumor gene in diverse cancer, including colorectal cancer [ 9 ]. Intriguingly, an existing study has reported that miR-497/195 could be inhibited in myoblasts, as well as skeletal muscle tissues by nuclear factor κB (NF-κB) [ 10 ], a transcription factor which is identified as a type of transcription factor dimer composed of p50/NFKB1, p52/NFKB2, c-Rel, p65/RelA as well as RelB [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggested that RAF can affect the proliferation of cell through in uencing the distribution of cell cycle [29][30][31], and we speculated that the signi cant and rapid change of estradiol level was caused by GCs proliferation. Our ow cytometry analysis results showed that RAF709 did not induce the suppression of cell cycle stage, but affected on the activity of estradiol synthase, which con rmed that RAF1 could regulate the expression of CYP19A1 [32] through the ERK signaling pathways [33].…”
Section: Discussionmentioning
confidence: 91%